Geometry and kinematic evolution of ductile shear zones in the Ersfjord Granite (1.79 Ga), West Troms Basement Complex: A Svecofennian accretionary thrust system - Haaland, Linda Cecilia (UiT Norges arktiske universitet, 2018)
The Ersfjord Granite is a 1.79 Ga felsic intrusion in the geological region of West Troms Basement Complex (WTBC). Its intrusion history and evolution relative to surrounding Neoarchean TTG-gneisses has until now been poorly understood, providing the basis for this thesis. The present study focuses on internal deformation structures in the granite, as well as the nearby Gråtind Migmatite, in order to propose a tectono-magmatic model for the granite, and to compare the deformation to existing relevant literature. The Neoarchean to Svecofennian deformation in the area can be summarized as follows: (i) Crustal shortening during the Neoarchean formed a well-foliated migmatitic fabric in the Gråtind Migmatite, prior to the intrusion of the Ersfjord Granite. (ii) The Ersfjord Granite intruded into the Neoarchean mid-crustal lithosphere in the late stages of the Svecofennian orogeny, creating a weak, distributed magmatic foliation. (iii) During, or shortly after, the intrusion of the Granite, WNW-directed thrusting formed low-angled, migmatitic shear zones in an accretionary orogenic setting involving partial anatexis. (iv) E-W directed crustal shortening folded the shear zones in the Ersfjord Granite and surrounding lithologies into open, upright folds, likely in the late stages of accretion. (v) A final deformation refolded the accretionary thrust systems into steeply plunging folds, in the Ersfjord Granite also leading to axial-planar strike-slip movement. A tentative correlation is proposed to the evolutionary history of WTBC as outlined by Bergh et al. (2010), suggesting that the Ersfjord Granite intruded into the Neoarchean crust in an accretionary island arc or subduction system, involving partial anatexis and mixing of crustal components. The Ersfjord Granite is proposed to be a part of an oblique, antithetic thrust to the main tectonic transport direction during the Svecofennian accretion in WTBC. It is further suggested that the intrusion and deformation of the Ersfjord Granite, as well as the WTBC, is a part ...